The use of intrastromal corneal ring segments in patients with myopia and keratoconus - Drzyzga, Łukasz; Wyględowska-Promieńska, Dorota; Piotrowska-Gwóźdź, Anna; Gościniewicz, Piotr; Mrukwa-Kominek, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Intrastromal corneal ring segments were primary used for correcting myopia ranging from -0.5 to -3.0 diopters. Nowadays, the most common indication of PMMA insertion in the world is keratoconus-associated astigmatism. The aim of this paper is to provide an overview of using of intracorneal ring segments in myopia and keratoconus. The addressed issues include commercially available ring models, indications and contraindications for ring implantation as well as the recommended surgical techniques. The efficacy of ring implantation in other conditions, such as post-LASIK ectasia and corneal transplantation is also discussed based on literature review. Additionally, the combined procedure of intracorneal ring segment implantation and corneal collagen cross-linking is mentioned as one of the latest trends.